การพัฒนาระบบสารสนเทศการจัดการเพื่องานติดตั้งและเคลื่อนย้ายโทรศัพท์สาธารณะ - พรทิพย์ สมสฤทธิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
Analyzes, designs and developes the Management Information System in order to manage the installation and relocation of public phone which will help entering, storing, retrieving and reporting data. It also can be used to display data as text and mapping. The Management Information System for Installation and Relocation of Public Phones consists of 5 Subsystems as follows: Site System, Public Booth System, Drop Wire System, Public Phone System and Electric System. Microsoft Access 97 RDBMS is used for storing data while Visual Basic 4.0 is used for application developing and MapInfo Application is used for map data storing. The outcomes of the research indicate the system above could create the better level of convenience, accuracy and acceleration during all involved work-units are proceeding